Transcriptome profiling of the posterior salivary glands of the cuttlefish Sepia officinalis from the Portuguese West coast - Gonçalves, Cátia; Moutinho Cabral, Inês; Alves de Matos, António P.; Grosso, Ana R.; Costa, Pedro M. (Frontiers in Marine Science, 2024)
Cephalopods like octopuses and cuttlefishes are known to secrete a ‘toxic saliva’ to inject into their prey, especially crustaceans since the XIX century. However, only in the mid-XX century were the first coleoid-specific toxins successfully isolated. Motivated by the growing interest on the global ocean as an almost inexhaustible source of novel bioactive compounds, we used RNA-Seq – based transcriptomics and de novo assembly of transcriptomes to screen the posterior salivary glands of Sepia officinalis (the common cuttlefish) from the Portuguese West coast for toxins and other bioactive proteins and peptides. Supported by microanatomical analyses, the posterior salivary glands constitute indeed the ‘venom gland’ whereas the more elusive anterior salivary glands (embedded in the buccal mass) are responsible for the production of mucin-rich saliva that is effectively the vehicle that transports the toxins as the venom is injected into the prey. Indeed, the transcriptomic profiling suggests that the cuttlefish venom is complex mixture of bioactive proteins, among which neurotoxins are major players, together with enzymes whose function is to digest the extracellular matrix to facilitate diffusion of the toxins. Nonetheless, by comparing with previous RNA-Seq data obtained from S. officinalis collected from other biogeographical areas, it may be suggested that significant inter-populational variation in venom composition can occur, which may potentially increase the span of bioactives secreted by these animals. We isolated and validated the full coding sequences for three important toxins, a cysteine-rich venom protein (CRVP), a venom insulin (VIns) and a cephalotoxin (CTX). The toxins seem to be relatively conserved among coleoids but diverging from other venomous mollusks such as cone snails. Their properties as potent modulators of glucose (in the case of VIns) and as potential neurotoxins (like CRVP and CTX) can render them primer targets for drug development.